2021
DOI: 10.3390/diagnostics11081483
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Quantitative Method for Tooth Grinding Surface Assessment Using 3D Scanning

Abstract: Sleep bruxism is an oral parafunction that involves involuntary tooth grinding and clenching. Splints with a colored layer that gets removed during tooth grinding are a common tool for the initial diagnosis of sleep bruxism. Currently, such splints are either assessed qualitatively or using 2D photographs, leading to a non-neglectable error due to the 3D nature of the dentition. In this study we propose a new and fast method for the quantitative assessment of tooth grinding surfaces using 3D scanning and mesh … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…The analysis of 18 standardized splints, each with eight grinding surfaces, revealed an intraclass correlation coefficient of 0.998. The authors concluded from their results that the proposed method was innovative, fast, and cost-effective and would support the initial diagnosis of SB [29]. However, the single-colour sheet applied in the cited study has to date never been validated regarding its capability to diagnose SB.…”
Section: Discussionmentioning
confidence: 94%
“…The analysis of 18 standardized splints, each with eight grinding surfaces, revealed an intraclass correlation coefficient of 0.998. The authors concluded from their results that the proposed method was innovative, fast, and cost-effective and would support the initial diagnosis of SB [29]. However, the single-colour sheet applied in the cited study has to date never been validated regarding its capability to diagnose SB.…”
Section: Discussionmentioning
confidence: 94%